The non-peptide neurokinin1 receptor antagonist, RP 67580, blocks neurogenic plasma extravasation in the dura mater of rats. - Shepheard, S. L. (1993)
A non-peptide neurokinin1 (NK1) receptor antagonist, RP 67580, that is selective for the rodent subtype of the NK1 receptor, dose-dependently reduced plasma extravasation in the dura mater produced by electrical stimulation of the trigeminal ganglion in rats, with an ID50 of 0.6 micrograms kg-1. Its enantiomer RP 68651 was some 400 fold less active. The results indicate that neurogenic plasma extravasation within the dura mater is NK1 receptor-mediated and suggest that NK1 receptor antagonists may have a role as antimigraine agents.